2007
DOI: 10.1038/sj.jcbfm.9600480
|View full text |Cite
|
Sign up to set email alerts
|

The Ammonium-Induced Increase in Rat Brain Lactate Concentration is Rapid and Reversible and is Compatible with Trafficking and Signaling Roles for Ammonium

Abstract: The glutamate-glutamine shuttle requires a flux of fixed N from neurons to astrocytes. The suggestion that some or all of this N is ammonium has received support from reports that ammonium (as NH 4 + ) rapidly enters astrocytes. Ammonium might also help control astrocyte energy metabolism by increasing lactate production. If ammonium has these functions, then its effect on brain metabolism must be rapid and reversible. To make a minimal test of this requirement, we have followed the time courses of the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
(74 reference statements)
3
8
0
Order By: Relevance
“…First, the release of lactate by pure astrocytes in culture during a 1-min exposure to NH + 4 was estimated using an enzymatic assay. Consistent with previous reports (20,23), a significant increase in extracellular lactate was observed at 5 mM NH + 4 . However, the enzymatic assay was unable to detect significant lactate release at 0.2 or 0.5 mM NH + 4 ( Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…First, the release of lactate by pure astrocytes in culture during a 1-min exposure to NH + 4 was estimated using an enzymatic assay. Consistent with previous reports (20,23), a significant increase in extracellular lactate was observed at 5 mM NH + 4 . However, the enzymatic assay was unable to detect significant lactate release at 0.2 or 0.5 mM NH + 4 ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…infusion of NH + 4 . In view of this result, NH + 4 was speculated to have signaling roles in the brain (20). The aim of the present work was to investigate this possibility.…”
mentioning
confidence: 97%
“…, ; Provent et al . ). Almost half (10) of the in vivo studies evaluated the effect of systemic administration of lactate (either as an acid or its sodium salt) on CBF in animals.…”
Section: Resultsmentioning
confidence: 97%
“…The majority of in vivo animal studies (Table S3) were conducted in mongrel dogs (Harper and Bell 1963;Iwabuchi et al 1973;Hermansen et al 1984;Young et al 1991), or rats (Hallstr€ om et al 1990;Ido et al 2001Ido et al , 2004Provent et al 2007). Almost half (10) of the in vivo studies evaluated the effect of systemic administration of lactate (either as an acid or its sodium salt) on CBF in animals.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…On the other hand, neurons constantly degrade PFKFB3 (Almeida et al, 2004; and reviewed in Bolaños et al, 2010) and neuronal activation of PFKFB3 was shown to lead to oxidative stress and neuronal apoptosis (Herrero-Mendez et al, 2009). Astrocytic-produced lactate was therefore proposed to alternatively fuel neurons for oxidative metabolism during neuronal activity, in line with stimulation of glycolysis by K + (Peng et al, 1994; Bittner et al, 2011), by glutamate (Pellerin and Magistretti, 1994), and increased lactate efflux by K + (Sotelo-Hitschfeld et al, 2015) and NH +4 (Provent et al, 2007; Lerchundi et al, 2015), while neuronal glucose to be diverted into the pentose phosphate pathway for antioxidant defense during enhanced work at the respiratory chain (Bouzier-Sore and Bolaños, 2015). The study by Sibson et al in the rat brain suggesting 1:1 stoichiometry between neuronal glucose oxidation and the glutamate-glutamine cycle rate (Sibson et al, 1998) provided support to this early view of compartmentation of brain metabolism.…”
Section: Glial Support To Cerebral Functionmentioning
confidence: 93%